Pertanggungjawaban Pidana terhadap Anggota TNI Yang Melakukan Tindak Pidana Desersi Pada Waktu Damai (Studi Putusan Nomor 22-K/Pm I-02/AD/IV/2020) - Br Sinamo, Mellyda Udut; Hasibuan, Abdul Lawali; Sitorus, Nanang Tomi (Universitas Medan Area, 2023)
The crime of desertion is the absence of a TNI member without the permission of his immediate superior, at a place and time determined by the service, and leaving the military service unit for 30 (thirty) days. The type of research in this writing is normative juridical. The data collection technique is carried out by means of library research and field research. Criminal responsibility of TNI members who commit the crime of desertion during peace time is based on evidence, witness testimony, defendant's testimony and based on the facts revealed in the trial. The judge's consideration in handing down a verdict against a member of the TNI who committed the crime of desertion during peace time, the defendant was charged using a single charge of Article 87 paragraph (1) Ke-2 Jo paragraph (2) KUHPM, the judge considered the facts in the trial such as the mitigating circumstances and the things that aggravated the defendant with the judge's conviction, so the decision handed down in this case was imprisonment for 5 (five) months.